Low Visceral Adipose Tissue Predicts the Outcome of Neoadjuvant Chemotherapy for Colorectal Liver Metastases: A Multicentre Real‐World Study - Yizhen Chen; Hangdong Jia; Rong Ye; Zhenyuan Zhou; Weijie Chen; Ming Zheng; Yuanyuan Zheng (Journal of Cachexia, Sarcopenia and Muscle)
ABSTRACT Background Visceral obesity (VO), associated with excessive visceral adipose tissue (VAT), has been extensively studied in cancer. However, whether low VAT can predict the prognosis of colorectal liver metastases (CRLM) undergoing neoadjuvant chemotherapy (NAC) remains unknown. Methods This multicentre real‐world cohort study analysed data from initially resectable CRLM patients who received NAC. The predictive effect of VAT on progression‐free survival (PFS) and overall survival (OS) was evaluated using restricted cubic splines (RCS). VAT was categorized into low/normal VAT and VO groups using X‐tile. The prognostic differences were further assessed through Kaplan–Meier (KM) analysis. The impact of changes in VAT (ΔVAT) after NAC was evaluated. Results Among 1524 CRLM patients, 1105 patients (72.51%) were under 65 years old, with a median VAT of 84.00 (36.24–148.00) cm2. Of all patients, 804 (52.76%) were female. A U‐shaped nonlinear relationship was observed between VAT and both PFS/OS (p < 0.001). Compared with the normal VAT, both low VAT and VO groups showed worsened PFS and OS (p < 0.05). The 3‐year PFS rate was 31.6%, 69.0% and 42.0% in the low, normal VAT and VO groups (p < 0.05). The 3‐year OS rate was 76.4%, 88.9% and 79.4% in the low, normal VAT and VO groups (p < 0.05). There was also a nonlinear relationship between VAT and NAC‐related adverse events, objective response rate and postoperative complications (p < 0.001). An increase in ΔVAT in the low VAT group was associated with better PFS and OS (p < 0.05). In the VO group, both increases and decreases in ΔVAT were associated with worsened PFS and OS (p < 0.05). Conclusions This study is the first to reveal that low VAT and VO can predict PFS and OS in CRLM patients undergoing NAC. Baseline VAT and ΔVAT may serve as important indicators for risk stratification and personalized treatment in CRLM patients.